ANALISIS PENGARUH PENGELOLAAN LAHAN PERTANIAN BERBASIS ADAT-ISTIADAT TERHADAP KESEJAHTERAAN MASYARAKAT - Liza Yani; Mukhlis M.Nur (Jurnal Ekonomi Pertanian Unimal, 2020)
Thish study aims to determine and analyze the influence of custumary-based  agricultural land management on the welfare of the community in gampong cemeucet,kuta makmur subdistrict,norsh aceh regency,this study uses primary data obtained from the distribusion of questionnairies to all reserch respondents.The sampling method used is the total sampling method and the number of samples  used is 30 respondent who have customary-based agricultural land.The data analysis menthod used is simple linear regression.The results partially show that custumary-based agricultural land management had an effect on on the welfare of the people  of gampong cemeucet,kuta makmur subdistrict,north aceh regency, this is evidenced by the value of t-count of 3,971 with a significant value of 0,000 which is higher  than t-table  with avalue of 1,701.